L’arte di abitare la terra. Roma, Palazzo delle Esposizioni, 24 febbraio 2012 - Vari, Autori (Il sogno della farfalla, 2012)
The inauguration of the book by the architect Ugo Tonietti, L’arte di abitare la terra (Rome, 2011), held on 24th February 2012 in Rome, at the Palazzo delle Esposizioni, provided the occasion for an in-depth and stimulating debate with the author on the nature and evolution of man, language, and artistic creation, which saw the participation of, among others, Massimo Fagioli and the philosopher and epistemologist Telmo Pievani, curator of the exhibit Homo sapiens. La grande storia della diversità umana (Homo sapiens. The great history of human diversity), which was being held contemporaneously in the same location.